Charter of the Commonwealth (2013)
Presents the text of the new charter, dated 14th day of December 2012; official signed on Commonwealth Day, 11 March 2013, by Her Majesty Queen Elizabeth II, Head of the Commonwealth.
Keywords: COMMONWEALTH